HPLC-UV Method for Simultaneous Determination of Moxifloxacin and Prednisolone Acetate in Eye Drops - Sireesha, K.R.; Prakash, K. (Asian Journal of Chemistry, 2012)
A simple, sensitive liquid chromatographic method was developed and validated for the simultaneous estimation of moxifloxacin and prednisolone acetate in bulk and pharmaceutical formulations. Optimum separation was achieved in less than 10 min using a C18 column (250 mm × 4.6 mm i.d, 5μ particle size) by isocratic elution. The mobile phase consisting of a mixture of mixed phosphate buffer (pH 6.8) and acetonitrile (50:50 v/v) was used. Column effluents were monitored at 265 nm at a flow rate of 1 mL/min. Retention times of moxifloxacin and prednisolone acetate were 3 and 4.2 min, respectively. The linearity of moxifloxacin and prednisolone acetate was in the range of 2-12 and 4-24 μg/mL respectively. Developed method was economical in terms of the time taken and amount of solvent consumed for each analysis. The method was validated and successfully applied to the simultaneous determination of moxifloxacin and prednisolone acetate in bulk and pharmaceutical formulations.